Factors associated with successful vaginal birth after a cesarean section: a systematic review and meta-analysis - Yanxin Wu; Yachana Kataria; Zilian Wang; Wai-Kit Ming; Christina Ellervik (BMC, 2019)
Abstract Background Evidence for the relationship between maternal and perinatal factors and the success of vaginal birth after cesarean section (VBAC) is conflicting. We aimed to systematically analyze published data on maternal and fetal factors for successful VBAC. Methods A comprehensive search of Medline, Embase, and the Cumulative Index to Nursing and Allied Health Literature, from each database's inception to March 16, 2018. Observational studies, identifying women with a trial of labor after one previous low-transverse cesarean section were included. Two reviewers independently abstracted the data. Meta-analysis was performed using the random-effects model. Risk of bias was assessed by the Newcastle-Ottawa Scale. Results We included 94 eligible observational studies (239,006 pregnant women with 163,502 VBAC). Factors were associated with successful VBAC with the following odds ratios (OR;95%CI): age (0.92;0.86-0.98), obesity (0.50;0.39-0.64), diabetes (0.50;0.42-0.60), hypertensive disorders complicating pregnancy (HDCP) (0.54;0.44-0.67), Bishop score (3.77;2.17-6.53), labor induction (0.58;0.50-0.67), macrosomia (0.56;0.50-0.64), white race (1.39;1.26-1.54), previous vaginal birth before cesarean section (3.14;2.62-3.77), previous VBAC (4.71;4.33-5.12), the indications for the previous cesarean section (cephalopelvic disproportion (0.54;0.36-0.80), dystocia or failure to progress (0.54;0.41-0.70), failed induction (0.56;0.37-0.85), and fetal malpresentation (1.66;1.38-2.01)). Adjusted ORs were similar. Conclusions Diabetes, HDCP, Bishop score, labor induction, macrosomia, age, obesity, previous vaginal birth, and the indications for the previous CS should be considered as the factors affecting the success of VBAC.